2011
DOI: 10.1016/j.ccr.2010.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of LMPP-like and GMP-like Leukemia Stem Cells in Acute Myeloid Leukemia

Abstract: The relationships between normal and leukemic stem/progenitor cells are unclear. We show that in ∼80% of primary human CD34+ acute myeloid leukemia (AML), two expanded populations with hemopoietic progenitor immunophenotype coexist in most patients. Both populations have leukemic stem cell (LSC) activity and are hierarchically ordered; one LSC population gives rise to the other. Global gene expression profiling shows the LSC populations are molecularly distinct and resemble normal progenitors but not stem cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

51
593
2
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 572 publications
(649 citation statements)
references
References 44 publications
51
593
2
3
Order By: Relevance
“…Whereas MDS has been shown to originate from the earliest haematopoietic stem cell (Lin‐CD34 + CD38 − CD90 + ) (Woll et al , 2014), recent evidence suggest the majority of AML cases to propagate from more mature progenitors (Mora‐Jensen et al , 2015). Furthermore, in AML more than one LSC population can co‐exist in the same patient and be hierarchically ordered (Goardon et al , 2011). Speculatively, in MDS, CD34 + CD38 − CLEC12A + cells could be a distinct CSC population downstream in a CSC hierarchy.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas MDS has been shown to originate from the earliest haematopoietic stem cell (Lin‐CD34 + CD38 − CD90 + ) (Woll et al , 2014), recent evidence suggest the majority of AML cases to propagate from more mature progenitors (Mora‐Jensen et al , 2015). Furthermore, in AML more than one LSC population can co‐exist in the same patient and be hierarchically ordered (Goardon et al , 2011). Speculatively, in MDS, CD34 + CD38 − CLEC12A + cells could be a distinct CSC population downstream in a CSC hierarchy.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that GMPs and lymphoid-primed MPPs both had leukemia-initiating potential and that these populations are organized in a hierarchical order. 44 Our murine AML model is perfectly suited to test the effects of chemotherapy and tyrosine kinase inhibitors blocking FLT3 ITD function on specific cellular populations to investigate their specific role in relapse of leukemia after complete remission. …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a hierarchy of cells can still be found to exist within these leukaemias 40 . In addition, perturbations of differentiation that affect normal lineage restriction processes (for example, as found in biphenotypic leukaemias), or the production of abnormal phenotypes, are well documented consequences of leukaemogenesis 41 .…”
Section: When a Clonal Hierarchy Is In Questionmentioning
confidence: 99%